The role of agricultural ashes (rice husk ash, coffee husk ash, sugarcane bagasse ash, palm oil fuel ash) in cement production for sustainable development in Africa - Susan K. Onsongo; John Olukuru; Onesmus M. Munyao; Onesmus Mwabonje (Discover Sustainability)
Abstract Ordinary Portland cement (OPC) is produced through energy-intensive processes and contributes to approximately 8% of global carbon dioxide emissions. As one of the most consumed materials after water, cement's environmental impact is substantial. Decarbonizing emissions in the intensive processes of cement production requires a sustainable supply of low-carbon resources. The purpose of this study is to explore the potential of agricultural waste ashes as supplementary cementitious materials (SCMs) to reduce the carbon footprint of OPC. In Africa, where agricultural waste is abundant, these residues could offer a sustainable solution for cement manufacturing. This study employed a multi-criteria decision analysis methodology to identify and select relevant literature for analysis. The review reveals that incorporating agricultural-based SCMs, such as rice husk ash, coffee husk ash, sugarcane bagasse ash, and palm oil fuel ash, into cement production can significantly reduce clinker requirements, thereby lowering carbon dioxide emissions while maintaining performance standards of OPC. The review found that locally sourced waste materials can reduce the carbon footprint of cement by up to 40%. Transitioning from a clinker-dependent sector to a bio-based one presents several opportunities as well as challenges for the African cement industry, but it is critical for reducing carbon emissions and improving sustainability. This approach not only decreases emissions but also supports sustainable construction, aligning with global climate goals and sustainable development goals (SDGs) 12 (responsible consumption and production) and 13 (climate action). Adopting green cement could revolutionize the African cement industry, promoting resource efficiency and sustainable development across the continent.